If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 + -28y = 40 Solving 63 + -28y = 40 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + -28y = 40 + -63 Combine like terms: 63 + -63 = 0 0 + -28y = 40 + -63 -28y = 40 + -63 Combine like terms: 40 + -63 = -23 -28y = -23 Divide each side by '-28'. y = 0.8214285714 Simplifying y = 0.8214285714
| 5x=4x-2 | | 8x^3-32x=0 | | 3x^2-10x-25=0 | | 4x^2-9x-28=0 | | -t-2=9(t-8) | | -1x+5=7 | | 6b=24 | | 63x^2-32x-63=0 | | y-1=3(x-13) | | 4x+10=26 | | 4(2x+9)-3=65 | | B+4=7(3) | | 0.4(5-04n)=-3.2 | | 3x+42=3(x-b) | | x^2-18=-3x | | 2w+13=63 | | 8z+7=79 | | .75x=6 | | (x+y)(3m-5n)= | | 10x-3x-1=4x+3 | | 3t^3+15t^2-2t-10=0 | | (x+4)(x+7)=0 | | (2a-c)(3b+5d)= | | 5x+y=672 | | 7n-2=29+6 | | (xy-2)(xy+4)= | | (x^2-y^2)(x-y)= | | 0.25(12-16q)=5(q+6) | | y=38x^6+29x^5+95x^4-x^3-4x^2+3x-1 | | 2x-4y=9 | | 1-5x=-2x+16 | | (2x+3y)(2x-5y)= |